Business Development Strategy Formulation for Tomoro Coffee Ciputat Raya Based on SWOT Analysis - Tio Febriawan; Pitri Yandri (CAKRAWALA : Management Science Journal, 2026)
The coffee industry in Indonesia has transformed into a representation of social identity and modern lifestyle, triggering intensive competition in the food and beverage sector. Tomoro Coffee Ciputat Raya Branch faces strategic challenges in maintaining a competitive advantage amidst high population density and fierce competition in South Tangerang. This study aims to formulate a business development strategy by identifying the company's internal and external factors. The research method employed is descriptive quantitative, utilizing Internal Factor Analysis Strategy (IFAS) Matrix, External Factor Analysis Strategy (EFAS) Matrix, and the SWOT Cartesian Diagram. Data were collected through field observations at Jl. Dewi Sartika No.11G and questionnaires distributed to six expert respondents. Identification results indicate that the primary strengths lie in the Eversys espresso machine technology, which ensures taste consistency (score 0.357), and a strong modern brand image (score 0.357). The most significant opportunities arise from the growth of the Gen Z population (score 0.416) and the sustainable Work From Cafe (WFC) trend (score 0.387). The data processing resulted in an IFAS score of 3.367 and an EFAS score of 3.194, positioning the company in Quadrant I (Aggressive). The recommended strategy is a growth-oriented strategy based on the Strengths-Opportunities (SO) approach, implemented through the optimization of digital market penetration via the Tomoro App and the enhancement of WFC supporting facilities to strengthen customer retention and create entry barriers for competitors.